The Effect of Therapy Massage Effleurage on Primary Dysmenorrhea in Adolescents - Putri Azzahroh; Triana Indrayani; Novita Lusiana (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The incidence of dysmenorrhea in Indonesia is quite high. Dysmenorrhea can be reduced both pharmacologically and non-pharmacologically. One of the non-pharmacological therapies is massage effleurage. Non-pharmacological pain management is safer because it does not cause side effects like drugs. After all, non-pharmacological therapy uses physiological processes. Objective to determine the effect of therapy massage effleurage on primary dysmenorrhea pain in adolescent girls at Posyandu Kenanga 2 Bojong Rawalumbu Bekasi in 2021.This pre-experimental study used a one-group post-test pretest design. The sample in this study amounted to 25 young women who experienced dysmenorrhea. The sampling technique used was the purposive sampling technique. The research instruments are SOP worksheets and pain level measurement sheets using the Numeric Rating Scale (NRS) which have been tested for validity and reliability in previous studies. The data will be analyzed using univariate and bivariate analysis with the Wilcoxon test. The results showed that massage effleurage on dysmenorrhea pain in adolescent girls significantly affected dysmenorrhea pain in adolescent girls, with a p-value = 0.000. There is an effect of Massage Effleurage on reducing primary dysmenorrhea pain in adolescent girls at Posyandu Kenanga 2 Bojong Rawalumbu Bekasi.